Striatal Proteomic Analysis Suggests that First L-Dopa Dose Equates to Chronic Exposure - Scholz, Birger; Svensson, Marcus; Alm, Henrik; Sköld, Karl; Fälth, Maria; Kultima, Kim; Guigoni, Céline; Doudnikoff, Evelyne; Li, Qin; Crossman, Alan R.; Bezard, Erwan; Andrén, Per E. (PloS one, 2008)
L-3,4-dihydroxypheylalanine (L-dopa)-induced dyskinesia represent a debilitating complication of therapy for Parkinson's disease (PD) that result from a progressive sensitization through repeated L-dopa exposures. The MPTP macaque model was used to study the proteome in dopamine-depleted striatum with and without subsequent acute and chronic L-dopa treatment using two-dimensional difference in-gel electrophoresis (2D-DIGE) and mass spectrometry. The present data suggest that the dopamine-depleted striatum is so sensitive to de novo L-dopa treatment that the first ever administration alone would be able (i) to induce rapid post-translational modification-based proteomic changes that are specific to this first exposure and (ii), possibly, lead to irreversible protein level changes that would be not further modified by chronic L-dopa treatment. The apparent equivalence between first and chronic L-dopa administration suggests that priming would be the direct consequence of dopamine loss, the first L-dopa administrations only exacerbating the sensitization process but not inducing it.